Impact of JPEG compression on the metrological characteristics of industrial CT data - Steffen Kieß; Robin Trostorf; Hieu Tran; Jajnabalkya Guhathakurta; Sven Simon; Ulrich Neuschaefer-Rube (e-Journal of Nondestructive Testing)
The basis of metrology with computed tomography (CT) are volume datasets with increasing sizes in the two- or three-digit GB range due to the increasing detector resolutions in the double-digit MPixel range. Handling these large amounts of data poses a considerable challenge in metrology in terms of sufficiently fast visualization, analysis and data transfer via networks (local networks or over the Internet) as well as cost- and energy-efficient archiving of TB to PB data volumes. Therefore, this work investigates the impact of lossy compression of volume data on the metrological quality of CT datasets using JPEG, which reduces the amount of data by more than one order of magnitude. The JPEG compression standard is used for compression here because it is available in CT voxel data viewers and its compression artifacts are well known from its widespread use for image compression. It is shown that the impact of JPEG compression artifacts on the metrological quality of CT datasets is limited, how the measurement uncertainty contribution due to compression can be determined and how its acceptability for metrology in general can be evaluated.